Cartel stability in times of low interest rates - Severin Lenhard (University of Bern, Department of Economics, 2021)
We study the interest rate's effect on the stability of cartels. A low interest rate implies a high discount factor and thus increases cartel stability. If firms access the capital market, an additional effect comes into play: a low interest rate lowers investment costs, resulting in more profitable deviations from the collusive agreement. We propose a new measure for a cartel's stability regarding the two opposing effects. Stability is U-shaped in the interest rate. We test our theory using a dataset of 615 firms and find supporting evidence. We conclude that the current unusually low interest rate facilitates collusion.
Keywords: C41; D43; K21; L40; 330; Collusion; Interest Rate; Repeated Game; Survival Analysis